ARABIC LITERATURE IN THE AGE OF GLOBALIZATION: TEXTUAL AND SOURCE STUDIES – A METHODOLOGICAL AND EDUCATIONAL APPROACH - Ayman Othman Abdel-Aleem Mohamed El-Shereey (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
This research aims to examine the position of Arabic literature in the age of globalization through two complementary axes: literary text studies and source studies, with a focus on the methodological and pedagogical dimensions of teaching Arabic literature, particularly in non-Arabic-speaking environments. The research stems from the central question: How can modern critical approaches be utilized without compromising the unique character of Arabic literary texts and their heritage? The research employs a descriptive-analytical methodology, relying on established critical references for analyzing texts and their sources.